2002
DOI: 10.1002/mds.10133
|View full text |Cite
|
Sign up to set email alerts
|

[18F]‐Dopa positron emission tomography imaging in early‐stage, non‐parkin juvenile parkinsonism

Abstract: There are few reports of positron emission tomography (PET) in juvenile parkinsonism (JP). We report on the results of (18)F-6-fluoro-L-dopa (FD) PET in a 14-year-old patient with JP of 5 years duration associated with atypical features. This is the youngest subject to be investigated to date. There was a severe asymmetric reduction in striatal FD uptake, with a rostrocaudal gradient in the putamen similar to that seen in adult-onset idiopathic parkinsonism. Extensive DNA analysis in this patient did not show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This result has partially been confirmed in another study, in which some, but not all, of the asymptomatic single parkin mutation carriers had significant PET changes (Khan et al 2002). Taken together, studies that utilize PET scans in cases without parkin mutations typically show similar results to cases with parkin mutations, illustrating the inability of PET to accurately predict parkin mutations (Pal et al 2002). However, similar to clinical findings, subtle differences between cases with and without parkin mutations may warrant further investigation and could reveal additional details of the pathogenic mechanisms associated with parkin mutations.…”
Section: Clinical and Pathological Findings In Parkin-linked Diseasesupporting
confidence: 54%
“…This result has partially been confirmed in another study, in which some, but not all, of the asymptomatic single parkin mutation carriers had significant PET changes (Khan et al 2002). Taken together, studies that utilize PET scans in cases without parkin mutations typically show similar results to cases with parkin mutations, illustrating the inability of PET to accurately predict parkin mutations (Pal et al 2002). However, similar to clinical findings, subtle differences between cases with and without parkin mutations may warrant further investigation and could reveal additional details of the pathogenic mechanisms associated with parkin mutations.…”
Section: Clinical and Pathological Findings In Parkin-linked Diseasesupporting
confidence: 54%
“…34 The K i reduction was asymmetrical in parkin patients, except for the caudate nucleus, whereas no interhemispheric asymmetry was noticed in nonparkin patients except in the posterior putamen. In a study of a single nonparkin patient, Pal et al 30 found an asymmetrical striatal decrease of fluorodopa F 18 uptake similar to that noted in idiopathic PD. However, this notion of asymmetry in our nonparkin group has to be considered cautiously because of the small number of patients.…”
Section: Fluorodopa F 18 Uptake In Parkin and Nonparkin Patientsmentioning
confidence: 56%
“…are also a few PET studies 30 performed in patients with YOPD but without genetically proven parkin gene mutations. The aims of this PET study were to analyze the pattern of fluorodopa F 18 uptake reduction in the striatum of a large population of YOPD patients and to correlate this pattern with the clinical characteristics of the patients and to determine if YOPD patients who carry parkin gene mutations (parkin patients) share specific abnormalities of fluorodopa F 18 uptake compared with YOPD patients without parkin mutation (nonparkin patients).…”
Section: Original Contributionmentioning
confidence: 99%
“…PET imaging of presynaptic terminal functions, therefore, reveals reduced radioligand uptake in the striatum of PD patients with a more pronounced decrease in the (posterior) putamen than in the caudate, and usually shows an asymmetry with more severe affection of the striatum contralateral to the clinically more affected limbs [8][9][10][30][31][32] . This pattern has not only been reported in sporadic PD but also in juvenile, young-onset parkinsonism and patients with parkin gene mutations [33][34][35] . Generally, significant correlations between disease severity and disability stages with the extent of the reduction in presynaptic terminal measures have been reported [15,31,36,37] .…”
Section: Pet Imaging Of Presynaptic Dopaminergic Functionsmentioning
confidence: 89%